In memoriam Academician, Prof. Dr. Dušan Čamprag (1925-2021) (Acta Entomologica Serbica, 2021)
Academician Dr. Dušan Čamprag, retired full professor of entomology at the Faculty of Agriculture, University of Novi Sad, passed away on March 22, 2021. With his passing, the scientific and professional communities lost one of the pioneers of plant protection in our country, a well-known entomologist and the oldest member of the Serbian Academy of Sciences and Arts (SASA).